Seguimiento a mujeres con resultado citológico positivo en una Empresa Social del Estado - ESE, Medellín, Colombia, 2011- 2012 (2017)
ABSTRACT: In Colombia, cervical cancer (CxCa) is one of the main causes of death. Every year, 7,000 cases are diagnosed and 3,300 deaths are recorded. 50% are because of late diagnosis and no access to specialized treatments. Objective: This study aims to monitor women who have had a positive cytological results in a state-owned company in Medellin from 2011 to 2012. Methodology: This is a cross-sectional descriptive study conducted on 277 women who had positive cytological results for lesions suggestive of high grade and/or glandular disorders. This research used stratified systematic sampling,and primary and secondary information sources. SPSS was implemented to systematize data like frequency, central tendency, and dispersion measurements were calculated. A descriptive univariate-bivariate analysis was implemented for sociodemographic and clinical related variables, and those related to the healthcare subjects received. Results: 10.7% of women with high grade or invasive lesions did not complete the treatment. The total monitoring opportunity was 52.3%, and the phases with the longest-waiting times were waiting for appointments for diagnosis and treatment. Conclusion: Despite efforts to improve screening coverage and to actively seek patients with a positive cytology evidenced in the study, there are still obstacles that impede patients’ prompt diagnosis and treatment, and this is something that in various cases leads to the progression of the disease and even death.